Multidimensional study on mitochondrial dysfunction in pulmonary hypertension - Yuan, Xuntao; Zhang, Yutao; Liu, Yuyan; Guo, Xiao; Jia, Shuying; Xiong, Xingquan; Sun, Xiuying; Jin, Zian (Frontiers in Medicine, 2025)
Pulmonary hypertension (PH), as a complex clinical syndrome, can be caused by multiple pathophysiological factors. Its characteristics are similar to hemodynamic abnormalities, significant increase of pulmonary artery pressure, contraction and remodeling of blood vessels, which eventually lead to serious complications such as increased pulmonary vascular resistance, hypertrophy of the right ventricle, and heart failure. The etiology of PH is multifaceted and highly variable, with a common pathological basis primarily characterized by mitochondrial dysfunction. Endothelial cell dysfunction, which directly impacts metabolism and function, is closely associated with PH and other lung diseases, making mitochondrial dysfunction the cornerstone of this condition. The therapy for PH primarily focuses on relaxing pulmonary blood vessels. However, existing vasodilation approaches struggle to effectively reverse the observed vascular remodeling process, which limits further therapeutic enhancement. Moreover, mitochondrial dysfunction represents a promising new direction of significant research in the treatment of PH. This review systematically combs the key molecular mechanisms of mitochondrial dysfunction in the pathological process of PH. The study focuses on multi-channel pathogenic mechanisms, including mitochondrial DNA (mtDNA) damage, electron transfer chain (ETC) dysfunction, protein homeostasis imbalance, defects in mitochondrial biogenesis, dynamic abnormality, and autophagy defect. Furthermore, this review summarizes recent research advancements targeting mitochondrial dysfunction as a potential intervention strategy for clinical treatment of PH. By integrating updated findings on molecular mechanisms with insights from existing literature, the study provides a comprehensive understanding of mitochondrial dysfunction’s role in PH pathogenesis and offers actionable evidence for developing novel therapeutic approaches.